Isolation of papain-soluble collagen from the skin of snake-head fish (Channa striata) - Andi Rahmayanti Ramli; Andi Rezky Annisa; Nur Alim Bahmid; Muhammad Dalvi Mustafa (jurnal1, 2020)
Snake-head fish (Channa striata) skin categorized a byproduct contains a higher concentration of collagen. The collagen can be extracted by using protease, which is known as Papain Soluble Collagen (PaSC). This study aimed to isolate the collagen from the snake-head fish skin using papain. The yield percentage and moisture content of PaSC in the skin was determined. Measurements using SDS-polyacrylamide gel electrophoresis (SDS-PAGE) and Fourier transform infrared spectroscopy (FTIR) were performed to characterize the PaSC and its functional groups. The results showed that the yields and moisture content of PaSC were 8.9% and 6.07%, respectively. The PaSC characterized by two α-chains appeared as collagen type I. Fourier transform infrared (FTIR) spectra of PaSC confirmed a triple-helical structure of collagen. The results indicated that snake-head fish skin could be used as potential resources of collagen and papain can be used as an alternative affordable enzyme.